Prospects and problems of environment across the millennium - National Symposium on Problems and Prospects of Environment in the New Millennium (2000 : Mangalore University); Madhyastha, M. N.; Sridhar, K. R.; Lakshmi, Ahana (Delhi : Daya Pub. House, 2003)
Contributed papers presented at National Symposium on Problems and Prospects of Environment in the New Millennium held at Mangalore University in December 2000.
Includes bibliographical references and index.
Keywords: Pollution -- Environmental aspects -- Congresses; Nature -- Effect of human beings on -- Congresses; Environmental health -- Congresses; Coastal zone management -- Congresses